Rethinking evil : contemporary perspectives - Lara, María Pía (University of California Press, 2001)
This innovative volume will be welcomed by moral and political philosophers, social scientists, and anyone who reflects seriously on the twentieth century's heavy burden of war, genocide, ethnic cleansing, and other evidence of people's desire to harm one another. María Pía Lara brings together a provocative set of essays that reexamine evil in the context of a "postmetaphysical" world, a world that no longer equates natural and human evil and no longer believes in an omnipotent God. The question of how and why God permits evil events to occur is replaced by the question of how and why humans perform radically evil acts.